Keterlibatan Orang Tua dalam Peningkatan Prestasi Pendidikan Anak Usia Dini - R, Nurhasanah (Jurusan Tarbiyah STAI Al-Gazali Bone, 2024)
This study examines the role of parental involvement in improving early childhood education achievement. The purpose of this study is to analyze the forms of parental involvement, its impact on children's achievement, and identify the factors that affect the effectiveness of these involvements. The research was conducted with a qualitative approach through systematic literature studies and in-depth interviews with parents, educators, and early childhood education experts. The results showed that active parental involvement had a positive correlation with an increase in early childhood academic and non-academic achievement. Effective forms of involvement include home-based tutoring, regular communication with teachers, and participation in school activities. This study provides practical recommendations for parents and educational institutions to optimize collaboration in supporting child development.